Development of Games Online Features Educandy to Children Aged 5-6 Years - Siti Nurjanah; Leli Fertiliana Dea; Muhammad Saidun Anwar (Bulletin of Early Childhood, 2022)
Recognizing letters is important to be developed in early childhood for the next child's language skills. By introducing letters to children, it is hoped that children can understand letters by knowing the sounds and shapes of letters. The learning media that will be developed in this research is an online game on the educandy. The purpose of this study was to determine the development of online games on the educandy to introduce characters to children aged 5-6 years at KB Darul Falah Terbanggi Besar. Types of research and development (research and development). The development procedure according to the Borg and Gall theory consists of seven stages, namely potential and problems, data collection, product design, expert testing, product revision, product testing, and product revision. Based on the results of the study, it can be concluded that, games feature educandy to introduce script to children aged 5-6 years at KB Darul Falah Terbanggi Besar, the development of online game feature educandy children are able to name symbols of letters that are known, children are able to recognize the sound of the initial letters of the names of objects in the vicinity. The Effectiveness of Using Online Games Features Educandy to Improve Literacy Skills for Children aged 5-6 years, namely after research was conducted at the Darul Falah Family Planning Terbanggi Besar, it was proven that the literacy abilities of early childhood can be categorized as starting to develop.